2015
DOI: 10.1089/brain.2014.0240
|View full text |Cite
|
Sign up to set email alerts
|

Altered Functional Connectivity Strength in Abstinent Chronic Cocaine Smokers Compared to Healthy Controls

Abstract: Past research involving cocaine and resting-state functional connectivity (RSFC) has shown altered functional connectivity within the frontal and between the frontal and other cortical and subcortical brain regions in chronic users of cocaine. However, there have been discrepancies in literature regarding the relationship between RSFC between brain regions and cocaine use behavior. This study explored the RSFC between brain regions in cocaine smokers abstinent from cocaine use for 72 h and healthy controls. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
3
18
1
Order By: Relevance
“…Increased FC was observed in the right angular gyrus and right SPG of BQ dependent individuals. Our results are similar to other cocaine studies that have demonstrated increased FC between frontal-temporal and frontal-parietal brain regions of abstinent chronic cocaine users (89). Similarly, compared to people who have never smoked and former nicotine smokers, current smokers had greater connectivity in the right superior parietal lobe located in the dorsal attention network (90).…”
Section: Differences Of Functional Connectivity In Chronic Bq Users Asupporting
confidence: 90%
“…Increased FC was observed in the right angular gyrus and right SPG of BQ dependent individuals. Our results are similar to other cocaine studies that have demonstrated increased FC between frontal-temporal and frontal-parietal brain regions of abstinent chronic cocaine users (89). Similarly, compared to people who have never smoked and former nicotine smokers, current smokers had greater connectivity in the right superior parietal lobe located in the dorsal attention network (90).…”
Section: Differences Of Functional Connectivity In Chronic Bq Users Asupporting
confidence: 90%
“…The duration of cocaine use was associated with lower rsFC between ventral tegmental area and thalamus/lentiform nucleus/nucleus accumbens [26], greater short-range and long-range functional connectivity density in the regions of the default mode network (DMN) [27], lower intra-network connectivity strength of sensory motor cortex [28], and greater inter-network connectivity strength between occipital-limbic brain regions [28]. Greater peak cocaine level was associated with greater rsFC between caudate and thalamus and between amygdala and insula, and with lower rsFC between amygdala and cerebellum [22].…”
Section: Relationship Between Brain Connectivity and Behavior Drug Umentioning
confidence: 99%
“…Greater recent cocaine use was associated with greater rsFC between striatum and DLPFC [23]. Greater cocaine use frequency and money spent on cocaine per week in abstinent CDs was associated with lower connectivity strength within occipital brain regions [28]. …”
Section: Relationship Between Brain Connectivity and Behavior Drug Umentioning
confidence: 99%
“…As seen from Table 2, the t value of node ORBinf.L, CAU.L, MTG.L, PUT, PAL and PCG.R are less than 0 in patients, which indicates that activation level of these regions are less than those in normal group, and the functional connection strength of patient is relatively small. The value of node PoCG.R, IPL.L, PCUN.R, PreCG and PCG.L are greater than 0, this shows that the activation of this part of the patient's [26][27][28][29][30] region is higher than the normal, and the functional connection strength is relatively large. As can be seen from Table 2, the Precuneus's statistical value is large, which shows that the degree of activation in the region has a greater degree of weakening of patient.…”
Section: Discussionmentioning
confidence: 99%